Black nativity [videorecording (DVD)] - Lemmons, Kasi; Whitaker, Forest; Bassett, Angela; Tyrese; Blige, Mary J. ([Publisher not identified], 2014)
A holiday musical that follows Langston as he journeys to New York City to spend the Christmas holiday with his estranged relatives. Unwilling to live by their imposing rules, a frustrated Langston is determined to return home to his mother, Naima. Langston embarks on a surprising and inspirational journey, and along with new friends and a little divine intervention, he discovers the true meaning of faith, healing, and family.